2021
DOI: 10.1039/d1sm00854d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric, ferroelectric, energy storage and mechanical energy harvesting performance of ZnO–PVDF composites induced by MWCNTs as an additive third phase

Abstract: The present work highlights an attempt of fabricating a nanocomposite by addition of multi-walled carbon nanotubes (MWCNT) as third phase into flexible ZnO-Poly(vinylidene fluoride) (ZnO-PVDF) composites. MWCNT played very important...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…The comparison result shows that the introduction of CNTs facilitates the transfer of external force in the polymer, which makes the external force more widely applied to the piezoelectric phase, improving the electromechanical coupling performance of the PCs. 56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison result shows that the introduction of CNTs facilitates the transfer of external force in the polymer, which makes the external force more widely applied to the piezoelectric phase, improving the electromechanical coupling performance of the PCs. 56…”
Section: Resultsmentioning
confidence: 99%
“…The comparison result shows that the introduction of CNTs facilitates the transfer of external force in the polymer, which makes the external force more widely applied to the piezoelectric phase, improving the electromechanical coupling performance of the PCs. 56 In conclusion, the addition of BCZT particles and CNTs into the PVDF matrix contributes to the enhanced power generation performance due to the following aspects: Firstly, the synergistic design of the piezoelectric phase and conductive phase promotes the transition of a phase and g phase into polar b phase. Secondly, the conductive phase can cause the redistribution of the poling electric field and improve the poling efficiency.…”
Section: Origin Of Enhanced Power Generation Performancementioning
confidence: 99%
“…The dielectric loss at low frequencies (100 Hz) of composite films was higher than that of pure PVDF‐HFP because of the interfacial polarization, which derived from the different dielectric constant between PVDF‐HFP and HImMg fillers 36,37 . We observed that the dielectric loss decreased as the frequency increased until 10 kHz and then sharply increased around 1 MHz, which originated from typical molecular motions in the PVDF α‐phase and the micro‐Brownian movement of the amorphous phase chain segments 38 …”
Section: Resultsmentioning
confidence: 74%
“…It is worth noting that the electroactive b-phase formation and In the composites, the primary characteristic peak for pure PVDF at 19.9 is displaced to a higher diffraction angle, con-rming the activation of the polar phase. 55 Fig. 6 represents the schematic rendering of the possible interaction between the positive surface charge of CsPb 2 Br 5 and the CH 2 -CF 2 dipoles of PVDF.…”
Section: Resultsmentioning
confidence: 99%